1999
DOI: 10.1046/j.1525-1438.1999.99048.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cyclin D1 gene (CCND1) polymorphism in epithelial ovarian cancer

Abstract: We have investigated the influence of CCND1 genotype on clinical outcome in 138 women with epithelial ovarian cancer. CCND1 genotypes were identified from peripheral blood DNA by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) analysis. Patient CCND1 genotypes were compared with clinical details including FIGO tumor stage, residual tumor volume, tumor histology and differentiation, response to chemotherapy, progression free interval, and survival. We observed no association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…However, findings are contradictory. Some of these studies indicated the association of CCDN1 G870A with cancer risk, prognosis, survival or characteristics of tumors such as larynx and oral cavity (Izzo, 2003), nonsmall lung cancer (Betticher et al, 1995), breast cancer (Yaylim-Eraltan et al, 2009), head and neck cancer (Zheng et al, 2001), ovarian cancer (Dhar et al, 1999), pituitary adenomas (Simpson et al, 2001). A meta-analysis which also includes our previous study (Yaylim-Eraltan et al, 2010), reported a significant association between colorectal cancer risk and G870A polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings are contradictory. Some of these studies indicated the association of CCDN1 G870A with cancer risk, prognosis, survival or characteristics of tumors such as larynx and oral cavity (Izzo, 2003), nonsmall lung cancer (Betticher et al, 1995), breast cancer (Yaylim-Eraltan et al, 2009), head and neck cancer (Zheng et al, 2001), ovarian cancer (Dhar et al, 1999), pituitary adenomas (Simpson et al, 2001). A meta-analysis which also includes our previous study (Yaylim-Eraltan et al, 2010), reported a significant association between colorectal cancer risk and G870A polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Ceschi et al (2005) observed that the heterozygous AG genotype significantly reduces the risk for breast cancer compared with the GG genotype; this association, however, was restricted to women with high intake of n-6 fatty acids, low intake of antagonistic marine n-3 fatty acids, or a total lack of the antioxidative GSTM1. Dhar et al (1999) showed that CCND1 polymorphism influenced disease progression and altered survival in a small subgroup of patients with epithelial ovarian cancer who initially responded to postoperative chemotherapy. Also, Kang et al (2005) observed that the CCND1 polymorphism was associated with an increased risk for endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The common G870A polymorphism in exon 4 of CCND1 modulates the frequency of alternative splicing and likely reduces transcript levels (Betticher et al 1995). Recent studies have shown that the G870A polymorphism is associated with elevated risks for breast, ovarian, and endometrial cancer (Ceschi et al 2005;Dhar et al 1999;Kang et al 2005). Also, several molecular epidemiological studies have examined the association between the G870A polymorphism of CCND1 and cervical cancer risk (Catarino et al 2008;Catarino et al 2005;Satinder et al 2008;Jeon et al 2005;Thakur et al 2009), but their results were inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneity was explored using subgroup analysis (10) with ethnicity (Asians and Caucasians) and cancer types. We have classified the cancer types in nine different categories including breast (13)(14)(15)(16)(17)(18)(19), colorectal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), gynecologic [ovarian (35), cervical (36), and endometrial (37)], digestive tract [oral (38)(39)(40), esophageal (41)(42)(43)(44), and stomach (45,46)], blood-related [acute lymphoblastic leukemia (47), mantle cell lymphoma (48), and non-Hodgkin's lymphoma (49)], genitourinary [bladder (50)(51)(52)(53), prostate (54,55), and kidney (56)], lung (57)(58)(59)…”
Section: Methodsmentioning
confidence: 99%